Improving Deaf and Hard of Hearing Students’ Achievements Using STS Approach: A Literature Review - Iva Nandya Atika; Ediyanto Ediyanto; Norimune Kawai (International Journal of Pedagogy and Teacher Education, 2018)
Science for all indicates that science should be accessible to all learners including deaf and hard of hearing (DHH) students, but they tend to struggle with developing abstract concepts of science optimally. Science, Technology, and Society (STS) approach is an interdisciplinary approach to science learning which is integrating science with technology and society aspects. Through STS approach, students become more interested in learning abstract concepts of science because they can apply the concepts throughout their daily living. The purpose of this study was to investigate whether DHH students improve their achievement levels of science specifically in the aspects of cognitive and affective via STS approach. A total of five journal articles from 2008-2016 written in English on the topic of science learning using STS approach were reviewed. This literature was collected via ERIC database. Then they were analyzed and interpreted in accordance with the objectives of the study. Based on the literature reviews, students experiencing STS instruction improve their achievements according to five STS domains in science learning. Due to learning via STS approach, students not only memorize the science concepts, but also enable to analyze scientific information as well as to apply it in their real-life situations, and set them on a path of life-long learning in science.Keywords: Achievements, Science Learning, Deaf and Hard-of-Hearing, STS Approach.